769 In Vivo Evaluation of Spinal Cord Perfusion Using Contrast-Enhanced Transcutaneous Ultrasound. (April 2023) - Shaaya, Elias; Leary, Owen P.; Sastry, Rahul; Zhu, Michelle; Persad-Paisley, Elijah; Seidler, Michael; Beland, Michael; Fridley, Jared
Abstract : INTRODUCTION: Ultrasound (US) imaging is cheap, portable, and widely available. It has been used in multiple medical disciplines, both as a means of diagnosis and therapy. Developing US as a platform for spinal cord perfusion monitoring in patients with spinal cord injury (SCI) would provide a cheap, accessible, and real-time platform for managing spinal cord perfusion in the acute setting. METHODS: Four patients with previous cervical decompression and instrumentation were evaluated at a single center with transcutaneous US. We included adult patients with at least 2 levels of continuous cervical laminectomies greater than 3 months prior to US and no history of SCI. The first two patients underwent US imaging without contrast and the second two patients underwent contrast-enhanced US imaging with Lumason, a microbubble agent. Imaging was performed by a board-certified radiologist with US expertise using a General Electric (GE) Logiq E10 ultrasound scanner ans a high frequency linear transducer. The study was approved by the institutional ethics committee. RESULTS: In the non-contrast study (n = 2), the dura, spinal cord, and vertebral body were apparent on US. Application of Doppler was insufficient to discern intramedullary perfusion, so contrast-enhanced ultrasound was pursued (n = 2). With contrast, anatomic structures were again visible, and we were able to quantify differential spinal cord perfusion within and between cross-sectional sections of the cord. We demonstrated spinal cord hemodynamic perfusion by measuring peak signal intensity and the time to peak signal intensity after microbubble contrast injection. Then, a time-intensity curve was created and the area under the curve was calculated as a surrogate of spinal cord perfusion. CONCLUSIONS: Contrast-enhanced US is a viable platform for monitoring spinal cord perfusion in patients who have undergone prior cervical laminectomies.